2016
DOI: 10.1002/anie.201603149
|View full text |Cite
|
Sign up to set email alerts
|

The Uranyl Cation as a Visible‐Light Photocatalyst for C(sp3)−H Fluorination

Abstract: The fluorination of unactivated Csp3–H bonds remains a desirable, challenging transformation for pharmaceutical, agricultural, and materials scientists. Previous methods for this transformation have used bench-stable fluorine atom sources; however, many still rely on the use of UV-active photocatalysts for the requisite high-energy hydrogen atom abstraction event. Herein, we describe the use of uranyl nitrate hexahydrate as a convenient, hydrogen atom abstraction catalyst that can mediate fluorinations of cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
110
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(113 citation statements)
references
References 39 publications
0
110
0
3
Order By: Relevance
“…Recently, Sorensen and coworkers demonstrated that uranyl nitrate hexahydrate was a competent hydrogen abstraction catalyst for the visible-lightmediated fluorination of C-H bonds. [94] Although the scope was limited to the fluorination of hydrocarbons, it provides a starting point for the further development of uranium-based catalysts. …”
Section: C(sp 3 )-H Substratesmentioning
confidence: 99%
“…Recently, Sorensen and coworkers demonstrated that uranyl nitrate hexahydrate was a competent hydrogen abstraction catalyst for the visible-lightmediated fluorination of C-H bonds. [94] Although the scope was limited to the fluorination of hydrocarbons, it provides a starting point for the further development of uranium-based catalysts. …”
Section: C(sp 3 )-H Substratesmentioning
confidence: 99%
“…First, the strong interaction between the 2p orbital of oxygen and the 5f and 6d primary valence shells of uranium make the ground state and excited state of UO 2 2+ chemically inert to oxygen molecules, [20] which might help to prevent undesired transformations caused by active oxygen species (Scheme 1b,l eft). [23] However,w ep hrased af ew hypotheses after detailed examination. [23] However,w ep hrased af ew hypotheses after detailed examination.…”
Section: Introductionmentioning
confidence: 99%
“…nitrate and carbonate), causing these reactions to be unselective . Recently, however, Sorensen and co‐workers reported the first use of photo‐excited uranyl in the selective fluorination of cycloalkanes in organic media (Scheme ) . Judicious choice of both organic solvent (CD 3 CN or acetone‐D 6 ) and anion (nitrate vs .…”
Section: Methodsmentioning
confidence: 99%
“…[7] Recently, however, Sorensen and co-workers reported the first use of photo-excited uranyl in the selective fluorination of cycloalkanes in organic media (Scheme 1). [8] Judicious choice of both organic solvent (CD 3 CN or acetone-D 6 ) and anion (nitrate vs. acetate) were crucial, and recent quantum mechanical calculations highlighted the complex interplay of singlet and triplet excited states in the reaction coordinate. [9] Subsequently, Azam and co-workers used a chiral salen 1 ligand to saturate the uranyl equatorial coordination plane, resulting in a photoactive complex that acts as a catalyst for the αcyanation of anilines (Scheme 1); [10] in this case, commercially available uranyl acetate, [U VI O 2 (OAc) 2 (OH 2 ) 2 ], shows no activity.…”
mentioning
confidence: 99%